Effect of electron beam irradiation doses in antioxidant activity and phenolic content of Portuguese chestnuts - Carocho, Márcio (2012)
The objective of this study was to analyse the effect of electron beam irradiation (0.5, I and 3 kGy) on the antioxidant activity of Portuguese chestnuts (Castanea saliva Mill.) using different in vitro assays, such as the 2,2- diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging activity, reducing power, inhibition of ~-carotene bleaching and inhibition of lipid peroxidation using thiobarbituric acid reactive species (TBARS). Total phenolics were determined by spectrophotometric assays. Irradiated samples seemed to preserve phenolics content and revealed higher antioxidant activity than the control sample. The most indicated dose to maintain antioxidants content, and to increase reducing power and lipid peroxidation inhibition was 1 kGy.